Odpowiedź :
Mordo łatwo:
5 - 6 = -1
-3 + 4 = 1
-2,5 - 3,5 = -6
-10 + 4,5 = 5,5
3,5 - ( - 5,5) = 3,5 + 5,5 = 9
7 + (-8,5) = -1,5
-1,5 + (-3) = -4,5
-9 - ( -2,5) = -9 + 2,5 = 6,5
-4 - ( -6,5) = -4 + 6,5 = 2,5
-5 - 334 = 329
-215 + (-413) = -628
523 + (- 712) = -211
114 - (- 25) = 114 + 25 = 139
- 316- (- 229) = -316 + 229 = -87
3,5 + (- 514) = -510,5
- 2,1 + (- 312) = -314,1
- 3,4 - (- 115) = -3,4 + 115 = 111,6
- 2 - 3 - 7 = 2
5 - 8 - 6 = 3
- 9 + 3 - 4 = -10
- 4 + 7 - 5 = -2
2 + (- 4,5) - (- 1,5) = -1
- 5 + (- 3) + (- 8) = -16
- 1,5 - 7 - (- 2) = -6,5
5,5 + (- 3) + (- 6,5) = -4
- 1 - (- 1) + (- 0,5) = -0,5
♡ ∩_∩
(„• ֊ •„)♡
┏━∪∪━━━━┓
♡ liczę na NAJ 。 ♡
┗━━━━━━━┛
Odpowiedź:
5 - 6 = - 1
-3 + 4 = 1
- 2,5 - 3,5 = - 6
- 10 + 4,5 = 5,5
3,5 - (- 5,5) = 9
7 + (- 8,5) = - 1,5
- 1,5 + ( - 3) = - 4,5
- 9 - (- 2,5) = - 6,5
- 4 - ( - 6,5) = 2,5
- 5 - 334= - 339
- 215+ (- 413) = - 628
523+ (- 712) = - 189
114- (- 25) = 139
- 316- (- 229) = - 87
3,5 + (- 514) = - 510,5
- 2,1 + (- 312) = - 314,1
- 3,4 - (- 115) = 111,6
- 2 - 3 - 7 = - 12
5 - 8 - 6 = - 9
- 9 + 3 - 4 = - 10
- 4 + 7 - 5 = - 2
2 + (- 4,5) - (- 1,5) = - 1
- 5 + (- 3) + (- 8) = - 16
- 1,5 - 7 - (- 2) = - 6,5
5,5 + (- 3) + (- 6,5) = - 4
- 1 - (- 1) + (- 0,5) = - 0,5
Szczegółowe wyjaśnienie:
(Mam nadzieję, że pomogłam)